Խորհրդանշական քաղաքականության հիմնախնդիրները Հայաստանում - Ստեփանյան, Վահագն (Լիմուշ հրատ.)
In the modern era, the role of symbolic politics is very important in the political life of Armenia. The article reveals the essence, content, functions, cultural and political foundations of symbolic politics and the range of problems related to symbolic politics implemented in Armenia.
Keywords: Քաղաքագիտություն